Miniaturize four‐port UWB‐MIMO antenna with tri‐notched band characteristics. Issue 5 (25th December 2020) - Pannu, Preeti; Sharma, Devendra Kumar
Abstract: In this article, a compact and high performance 4‐port ultra‐wideband multiple‐input multiple‐output antenna is presented. The proposed antenna is designed by using a novel technology which includes integration of four orthogonal octad‐shaped radiators, four D‐shaped ground planes, multi‐stub techniques and slot techniques. The overall size of the design is effectively miniaturized and the ultra‐wideband characteristics are achieved through feed line tapering and by inserting slot in the D‐shape ground structure. Moreover, tri‐band notch characteristics are achieved in the proposed design by embedding L‐shaped stubs in the octad radiating elements. This results in impedance bandwidth of 2.6‐12.2GHz with notched characteristics at bands ranging from 3‐3.7GHz, 5‐6GHz and 7.9‐8.3GHz. In addition, the antenna shows high isolation and good diversity performance in terms of Envelop Correlation coefficient, Diversity gain and Total active reflection coefficient. A good trade‐off of performance has achieved from the proposed design makes it best candidate for wireless communication applications.